Histone Acetylation Dynamics during In Vivo and In Vitro Oocyte Aging in Common Carp Cyprinus carpio - Waghmare, Swapnil Gorakh; Samarin, Azin Mohagheghi; Samarin, Azadeh Mohagheghi; Danielsen, Marianne; Møller, Hanne Søndergård; Policar, Tomáš; Linhart, Otomar; Dalsgaard, Trine Kastrup (International journal of molecular sciences, 2021)
Aging is the most critical factor that influences the quality of post-ovulatory oocytes. Age-related molecular pathways remain poorly understood in fish oocytes. In this study, we examined the effect of oocyte aging on specific histone acetylation in common carp Cyprinus carpio. The capacity to progress to the larval stage in oocytes that were aged for 28 h in vivo and in vitro was evaluated. Global histone modifications and specific histone acetylation (H3K9ac, H3K14ac, H4K5ac, H4K8ac, H4K12ac, and H4K16ac) were investigated during oocyte aging. Furthermore, the activity of histone acetyltransferase (HAT) was assessed in fresh and aged oocytes. Global histone modifications did not exhibit significant alterations during 8 h of oocyte aging. Among the selected modifications, H4K12ac increased significantly at 28 h post-stripping (HPS). Although not significantly different, HAT activity exhibited an upward trend during oocyte aging. Results of our current study indicate that aging of common carp oocytes for 12 h results in complete loss of egg viability rates without any consequence in global and specific histone modifications. However, aging oocytes for 28 h led to increased H4K12ac. Thus, histone acetylation modification as a crucial epigenetic mediator may be associated with age-related defects, particularly in oocytes of a more advanced age.
Keywords: histony; stárnutí; histonacetyltransferasy; Carps; Histone Acetyltransferases; acetylace; Histones; Aging; kapři; Animals; oocyty; Acetylation; Protein Processing, Post-Translational; zvířata; posttranslační úpravy proteinů; Oocytes